Inside the defensive playbook: pick-and-roll tactical adjustments impact the external and internal loads during small-sided games in female basketball players - Qarouach, A.; Sansone, P.; Pernigoni, M.; Kreivyte, R.; Conte, D. (International Journal of Sports Physiology and Performance, 2024)
Purpose: This study aimed to assess the effect of playing different pick-and-roll (PnR) defensive tactical options during small-sided games (SSGs) on external and internal loads in female basketball players.